The Idea of Political Independence of Lithuania - Vėbra, Rimantas (Problemos, 1970)
The author undertakes the task to reveal – on the basis of available materials in the articles of the Lithuanian bourgeois periodical press of the second half of the 19th century and some other sources – the conception and evolution of the idea of the foundation of the independent Lithuanian state. Attention is focused mainly on the analysis of the attitude of the liberal ideological trend. The author notes that the political programme of the Lithuanian bourgeoisie existed already at the period in question. The minimum programme insisted upon the autonomy of Lithuania, the maximum one – upon the foundation of the independent Lithuanian state. Theses of the natural law theoreticians provided theoretical basis of the idea of political independence. The struggle of the enslaved peoples of Turkey, Austria-Hungary for national independence played a significant role as well.